Simulation of an automated blanking, stamping and bending process using automation studio for industrial application - L. Abdullah; P. B. Tiew; P. L. Soh (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.